Kajian Penggunaan Baja Tahan Karat 316L sebagai Implan Sendi Panggul - Muhammad Aldy Hassan; Luhadi Satriawan; Jhonsen Taharuddin; Mardiyati Mardiyati; Steven Steven (Faculty of Mechanical and Aerospace Engineering, 2023)
Implant is one of the most important innovations in medical devices to help people with disabilities or injuries, one of them is the hip-joint implant. The hip-joint implant must-have properties such as good corrosion resistance, good biocompatibility, and good wear resistance. These properties are important for maintaining safety during surgery and future use. Nickel-free 316L stainless steel is one of the materials that is commonly used as implants and meets all the requirements for a material to be used as an implant. 316L stainless steel also has an advantage, a lower price than titanium and cobalt. However, 316L stainless steel has low wear resistance and needs to be coated in order to improve its wear resistance. Recent research reported that the metallic glass FeCrMoCB was able to cover cronidur30 and improved its wear resistance. This study discussed the properties of 316L stainless steel implants, the testing process, the manufacturing process, and the sustainability aspects of the manufacturing process.